Echoes of the Holocaust in Leonard Cohen’s art - Adamskich, Karolina (Scripta Neophilologica Posnaniensia, 2019)
Leonard Cohen is mostly known as a singer-songwriter. Although his poems and novels are not as widely recognized as his music, it has been frequently argued that The Favourite Game (1963) and Beautiful Losers (1966) can be viewed as the most innovative and experimental novels to be published in Canada. They are also among the first representatives of Canadian postmodernism in literature. The main purpose of this article was to explore echoes of the Holocaust in Cohen’s novels, as well as in his book of poetry Flowers for Hitler (1964). Despite the fact that the links and allusions to Judaism made by him have been often stressed by the critics, what is demonstrated here is the fact that for Cohen, his Jewish heritage was not only a source of inspiration but also doubt and anger. This paper, apart from presenting the artist’s cultural and spiritual background, aims at demonstrating ethical ambivalences in Leonard Cohen’s art and examining the reasons behind the ambivalence, as well as discussing his works in the context of postmodern ethical theory.